Mentoring Asian graduate students who attend communication sciences and disorders programs in the United States. - Tsai M; Scherz J; DiLollo A (Perspectives on Issues in Higher Education, 2009)
This qualitative study provided an overview of American faculty members' perceptions of Asian graduate students who are in Communication Sciences and Disorders (CSD) programs in the United States. American faculty members with experience working with Asian graduate students in CSD programs were interviewed to identify their experiences with Asian graduate students compared to those with American students. Further, faculty members were asked about skills that were most helpful in mentoring Asian graduate students. Results yielded a variety of common themes across participants that were classified into three major categories: characteristics of Asian graduate students, English language skills, and teaching and mentoring changes or modifications. Moreover, four primary mentoring skills were identified, including cultural understanding, person-oriented, support system, and reconfirmation.